Exclusão e inclusão de votos nas eleições para a Câmara Municipal de Pelotas (RS) no período 1988-2008 - Rotta, Arthur Augusto (2012)
This research intends to analyze the proportional system using the elections for city council members in Pelotas as a model. Accordingly, its basis are the theoretical and political origins of the system of proportional representation in the democratic world and more specifically in Brazil. The study aims to verify in practice, if the purpose of the system designed for the municipal elections reaches its main intention, which is to ensure a broad representation of the electorate. This objective is achieved by analyzing the impact of electoral rules in the results of elections for city council members in Pelotas - from 1988 until the last one, occurred in 2008. In this period there were changes related to the characteristics of the electoral system , especially regarding to the electoral magnitude and formula. The comparative analysis of these claims, when verified the exclusion degree obtained by the electoral system, made possible to demonstrate in a more precise way how the change in certain characteristics of the Brazilian proportional system impacted the final results of the representation. In addition, it could highlight the importance of certain characteristics in combination in the electoral system